Application of Geo-informatics for Study Diversity the Plants of Rubiaceae in Phu Faek Forest Park, Kalasin Province - Prasertsri, Narueset; Sangpradid, Satith; Chusritong, Damrongsak; Haekan, Titthiyakan (Journal of Applied Informatics and Technology, 2022)
This research aimed to 1) Applied Geoinformatics for Study the diversity, density and distribution of Rubiaceae. 2) Spatial analysis and mapping the plants of Rubiaceae. The 50 temporary plots were laid out in this area by the size 40 X 40 meters. The results found that 14 species and can be divided into 2 types were followed by 1) Perennial 9 species. The most common was (Rothmannia wittii (Craib.) Bremek.) (Morinda coreia Buch.-Ham) and (Mitragyna hirsuta Havil.) The numbers of, the trees was 59, 39, and 28 trees, respectively. The Importance Value Index (IVI) was 3.638, 2.722, and 2.062 trees, respectively. The least found was (Ceriscoides turgida.) (Gardenia sootepensis.) and Adina cordifolia Hook. The numbers of trees was 2, 2, and 2 trees respectively. The (IVI) was 0.235, 0.141, and 0.141 trees, respectively. 2) There are 5 types of ground seedling types (Tamilnadia uliginosa (Retz.) Tirveng. & Sastre) (Canthium berberidifolium Geddes) (Gardenia obtusifolia Roxb. ex Kurz) (Paederia foetida L) (Oldenlandia corymbosa L.), the numbers of trees was 78 48 12 5 and 3 trees respectively. The density analysis by using Kernel method. The results found that 1) the perennial (sapling and tree) had the highest value between 0.014 – 0.020, lowest value between 0.005 – 0.008 tree per square meter. 2) the seedling was a perennial had the highest value between 0.115 -0.204 lowest value between 0.000 – 0.045 tree per square meter. 3) the seedling and ivy plants had the highest value between 0.016 – 0.021, lowest value between 0.001 – 0.006 tree per square meter, and the density analysis by using IDW method. The results found that 1) the perennial (sapling and tree) had the highest value between 0.011 – 0.019, lowest value between 0.000 – 0.002 tree per square meter. 2) the seedling as a perennial had the highest value between 0.081 – 0.152, lowest value between 0.000 – 0.015 tree per square meter. 3) the ivy plants had the highest value between 0.018 – 0.034 lowest value between 0.000 – 0.002 tree per square meter. The results of Analysis by using the Kernel Density technique will have Rubiaceae distribution with the data from colleeted in the field. When considering physical factors, the normalized difference water index (NDWI) was found that the Rubiaceae are present, in the value range 0.271 to 0.414. Which in the lowest humidity. The plants of the Rubiaceae have been discovered all across the mix-deciduous forest. The slopes faetor found the in ranging 10% to 20%. And the height faetor found that in range of 250 to 290 meters. The benefits of Rubiaceae there au very much use home, tools herb and ornamented plant. Therefore very deserving of conservation.